PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR PPKn SISWA MTs S AL ISLAM RUMBIO KABUPATEN KAMPAR - Nurhayati Nurhayati; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Meanwhile the benefits from this study, namely theoretical benefits,the study is expected to be able to provide contributions of thinking and materials in theworld of education in the world of education in the world. The practical benefits ofnamely as one of the requirements for obtaining educational scholars in the study ofpancasila and citizenship. Sample in the research is a student in the MTs S Al IslamRumbio Kampar District as which of 60 respondents are determined in technique TotalSampling. Data collecting instruments, observational quiries, and interviews. Dataprocessing with quantitative analysis using quantitative formula regression in simpleline with the help of 16 version of the SPSS app. By stating the hypothesis, there is aeffect between the family environment and the achievements of the students PPKn MTsS Al Islam Rumbio Kampar District. Based on research results About the effect familyenvironment and the achievements of the students PPKn MTs S Al Islam RumbioKampar District. Be found the effect family environment and the achievements of thestudents PPKn MTs S Al Islam Rumbio Kampar District in the amount of 95,56%.Key Word: The Effect, Family Environment, Learning Achievement